Study of DNA for molecular analysis and biochemical markers from non-invasive samples in beta-thalassaemia major patients / Mohd Rashdan Abd Rahim - Mohd Rashdan, Abd Rahim (2015)
Beta-thalassaemia is a common genetic disorder in Malaysia. It is a haemolytic anaemia which is caused by mutations within the β-globin gene complex, affecting the synthesis of β-globin chains. This will result in excessive free α-globin chains causing α-globin chain toxicity. Erythropoiesis is also impaired leading to chronic anaemia. Beta-thalassaemia major babies may appear healthy at birth. However, symptoms such as jaundice and anaemia will start to develop as they reach six months of life. They require frequent transfusions to maintain haemoglobin levels which lead to iron-overload. Although chelation therapy is recommended, the patients are still under oxidative stress. Patients need to be monitored during their therapy to prevent any organ damage and mortality due to oxidative injuries. The current sampling method used to diagnose and monitor the β-thalassaemia major patients involved the use of venous blood. The sampling method is invasive and requires a phlebotomist to perform the procedure with minimal pain to paediatric patients. Assessment of non-invasive methods as alternative sampling procedure will be advantageous for the molecular and biochemical analysis of β-thalassaemia. The present study aims to genotype purified DNA extracted from non-invasive samples including mouthwash, saliva and buccal cytobrush samples and to assess the biochemical markers from saliva samples. Samples were collected from β-thalassaemia major patients in University Malaya Medical Centre and healthy individuals. DNA was extracted using two alkaline lysis DNA extraction methods followed by organic purification to compare the concentration and purity. The purified DNA was amplified using various DNA amplification methods available to detect β-globin gene mutation present in the Malaysian population. Saliva samples were assessed for total non-enzymatic antioxidant capacity, level of protein and lipid peroxidation, activity of glutathione peroxidase (GPx), level of uric acid (UA) and iv cytokines tumor necrosis factor-α (TNF- α) and interleukin-6 (IL-6). Biochemical parameters were further analysed using parametric and non-parametric statistical analysis. Saliva samples provided highest amount of purified DNA compared with mouthwash and buccal cytobrush samples. In contrast, the DNA purity was the highest from mouthwash samples. DNA extraction Method 2, which used higher concentration of lysis agents and additional purification steps compared with Method 1, provided purified DNA with better reproducibility. The surface area of sample collection site and the amount of leukocytes may have contributed to the high purified DNA concentration while the amount of mucin contributed to the purity. The level of GPx was higher in β-thalassaemia major patients. Strong correlation was also observed between ferric reducing antioxidant power (FRAP) assay and UA. When the β-thalassaemia major patients group was further sub-divided, there was a notable difference in the level of AOPP between genetic classification of β-thalassaemia and the level TNF-α between ethnicity and age groups. Better chelation due to combination therapy, compliance, education and patient management may have helped in improving the oxidative stress status in β-thalassaemia major patients. In conclusion, mouthwash and saliva can provide high quality purified DNA for reproducible molecular analysis and biochemical parameters in saliva samples are within detectable limits for biochemical assays.